Morphologic Diversity of Martian Ripples: Implications for Large‐Ripple Formation. Issue 19 (12th October 2018) - Lapotre, M. G. A.; Ewing, R. C.; Weitz, C. M.; Lewis, K. W.; Lamb, M. P.; Ehlmann, B. L.; Rubin, D. M.
Abstract: Large ripples with meter‐scale wavelengths are ubiquitous across Mars. Curiosity 's traverse of the Bagnold Dune Field revealed a morphologic diversity of large Martian ripples that helps constrain their formative mechanism. Large ripples develop in isolated fields and on dunes. They form transversely and obliquely to longitudinally to the net sand‐flux direction in unimodally and bimodally distributed very fine to very coarse sand. They have either straight or sinuous crestlines. Inactive ripples are covered with dust, whereas migrating ripples are dust free. Here we present a unifying view of ripples that form in near‐bed sediment‐transport conditions (encompassing fluid‐drag and coarse‐grained ripples) to explain the range of large‐Martian‐ripple morphologies and expand the use of bedforms as environmental indicators. Plain Language Summary: Large sand ripples with meter‐scale crest‐to‐crest spacings abound on the Martian surface but are not found in terrestrial sandy deserts. Along its traverse through the Bagnold Dune Field, the Curiosity rover witnessed a rich diversity of such large ripples, both in terms of their shape and of their behavior. Rover observations help understand how these mysterious large Martian ripples form. Here we present a unifying view of ripples that form when grains are mobilized near the sediment bed by various fluids and across planets. Such an understanding of the formation mechanics of similar ripples will enable scientists to use the ripples' imprints on landscapes and in rocks to infer modern and past environmental conditions. Key Points: Martian ripples are diverse in morphology, dynamics, and activity Large Martian ripples belong to a family of bedforms that forms when a significant fraction of sediment transport occurs near the bed Near‐bed‐transport bedforms are found across environments and planets and may prove useful quantitative paleoenvironment indicators